Novel Passive Islanding Detection Technique by Monitoring Reverse Power at PCC. (5th May 2022) - Usman, Muhammad; Raza, Safdar; Munir, Hafiz Mudassir; Riaz, Mughees; Bukhari, Syed Sabir Hussain; Ro, Jong-Suk
Abstract : Power System of the age has included remarkable contribution of distributed energy resources (DERs). This inclusion has opened new era of research and studies. Islanding detection has become one of the important events in power system that is to be detected precisely. This study introduces a single-parameter-based passive technique for islanding detection which has zero nondetection zone without involvement of any signal processing tool. The proposed technique is tested for various islanding and nonislanding events. The simulation results prove that the suggested technique detects islanding event accurately and it is capable of distinguishing islanding and nonislanding events by an economical and simpler method.